Science, Folklore, and Ecology of Knowledges in Aoyama’s Detective Conan Anime - Quintairos-Soliño, Alba; Ojeda García, Francisco Miguel (Íkala, Revista de Lenguaje y Cultura, 2024)
During the Anthropocene, science and folklore have been efficient explanatory models of the world. However, numerous studies suggest a convergence of both perspectives in contemporary mass media productions, being Japanese animation a clear example. The aim of the research presented here was to analyse how science and folklore are integrated and opposed in Aoyama’s Detective Conan, an anime where cases often happen in rural Japan and where folk references confront Conan’s detective reasoning. To reach this objective, a comprehensive qualitative and quantitative study of the presence of folklore in this work—through aspects such as characterisation or narratives—was conducted in 75 cases and over 155 episodes which include references to folklore in their background, plot, or characters. The analysis revealed that, when folklore and science interact, rational thinking is usually preferred over folk beliefs; characters are stereotyped according to their genre or origins; and, more importantly, supernatural beliefs can be included in detective fiction without being ridiculed by the most rational characters.